Patent Thickets, Licensing and Innovative Performance - Elisabeth Müller; Megan J. MacGarvie; Iain M. Cockburn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
We examine the relationship between fragmented intellectual property (IP) rights and innovative performance, taking into consideration the role played by in-licensing of IP. Controlling for a variety of firm and market characteristics, we find that firms facing more fragmented IP landscapes are more likely to report expenditures on in-licensing and for those firms that do incur license costs we find a weak positive association between licensing expenditure and fragmented IP rights in the relevant technology. We also observe a negative relationship between IP fragmentation and innovative performance, but only for firms that engage in in-licensing and only for product innovation. The relationship between fragmentation and innovative performance also depends on the size of a firm's patent portfolio, which suggests an important strategic role for defensive patenting in the context of fragmented property rights.
More recent version: http://hdl.handle.net/10419/29635
Keywords: O34; O31; 330; patent thickets; licensing; innovative performance; Patent; Innovationswettbewerb; Lizenzvergabe; Immaterialgüterrechte; Innovation; Deutschland